Manifestations of Tradition Objection among the Bataks - Hermina Sutami (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
This paper tries to find out kinds of emotions appearing from the novel Penakluk Ujung Dunia (Conqueror of the World's Cape). lt told us about the struggle for land among Batak ethnic groups near Lake Toba a long time ago, triggered by the population growth. One ethnic group defeated another under a young commander, Ronggur. They did not only seize the enemies teritory, but also their women and children. One of them, Tio, became Ronggur's slave. He actually disagreed with the way of enlarging territory by attacking others. He believed—he got it from his dream—that someone had asked him to go along the river to its end to find a "new world". The chief and all villagers did not agree with him, because it was the place of their gods. Human being was prohibited to go there. His violation made him banished from his tribe and lost all his rights and sentenced to death. But, he managed to escape and carry on his intention by rowing along the river accompanied by Tio-who later became his wife. This novel expresses the mental structure of one culture in Indonesia at a certain time. By doing textual analysis on verbal and non-verbal expression through words, phrases, and sentences, we could describe the emotional condition of the Batak ethnic group at a certain time. Textual approach in this research is not only based on psychology. It also uses language as symbolic means.